Promoting Human Rights in Educational Sector in Nigeria: Trend of Student's Participation - Uche Nnawulezi; Bosede Remilekun Adeuti (The Indonesian Journal of International Clinical Legal Education, 2022)
The issue as to whether students are holders of rights in the changing faces of higher education in Nigeria has been a subject of great debate by scholars in human rights law and educational administration. These debates relate to whether students only have an interest which should be protected or a choice which can be exercised as right holders. However, the choice of exercising this interest is inherent in the student’s right to participation which entails a right to express a view especially in areas of decision making relating to education and welfare. The author noted in this study that even though issues of student’s welfare and education are engaged on the platform of rights, there is controversy as to whether students should participate in decisions that will change the face of higher education. This paper argues that adopting a right-based approach which recognizes the evolving competence of students and that allows full participation of students in decision making process in higher education in these respects strictly complies with international human rights practices on right to education. The paper concluded by making some recommendations useful to tackle the technical and legal intricacies occasioned by a weak educational culture.